The Effect of Organizational Climate and Work Motivation on Employee Performance at Sawerigading Hospital Palopo - Ahmad Syarief Iskandar Syarief; Nurul Inayah Iskandar; Muhammad Nur Alam Muhajir; Takdir (Jurnal Economic Resource, 2022)
This study aims to determine the effect of organizational climate and work motivation on employee performance. This research was conducted at Sawerigading Hospital, Palopo City, South Sulawesi. This study uses a population of all employees in Sawerigading Hospital, Palopo city as many as 378, people with a sample of 194 employees drawn by the Simple Random Sampling technique using the Slovin formula. Data collection techniques are carried out to obtain the required data and information using a questionnaire. Data analysis in this study used Multiple Linear Regression Analysis through the Statistical Package for Social Setence (SPSS.23) Program. The results of this study indicate that organizational climate has a positive and significant effect on the performance of employees at Sawerigading Hospital, Palopo City,